A New Density Model of Quartz Solubility in H2O-CO2-NaCl Ternary Systems up to High Temperatures and High Pressures. (13th February 2021) - Deng, Weiping; Wei, Qing; Liu, Xuan
Abstract : A novel density model for computing quartz solubility in H2 O-CO2 -NaCl hydrothermal fluids applicable to wide ranges of temperature and pressure is proposed. Based on the models of Akinfiev and Diamond (2009) and Wei et al. (2012), the effective partial molar volume of water (V H 2 O ∗ ) is replaced by the partial molar volume of water (V ¯ H 2 O ) by implementing an empirical correction, and water molar fraction (x H 2 O ) is modified with water activity (a H 2 O ), in addition to a series of changes to the model coefficient forms. The absolute values of averaged relative deviation of this model compared to the experimental data sets in pure water, H2 O-CO2, and H2 O-NaCl solutions are 5.74%, 6.69%, and 7.09%, respectively, which are better than existing models in the literature. The model can be reliably used for computing quartz solubilities in pure water from 0°C to 1000°C, from 0 bar to 20, 000 bar, and in CO2 - and/or NaCl-bearing solutions from 0°C to 1000°C, from 0 bar to 10, 000 bar (with slightly lower accuracy at 5000-10, 000 bar in H2 O-NaCl systems) in the single liquid region. Moreover, the trends and overall ranges of this model may probably be more accurate in the H2 O-CO2 -NaCl fluid mixtures compared to the limited experimental data. In addition, a bisection algorithm for deriving the isopleths of quartz solubilities based on this new model is first proposed, and application perspectives are discussed for various geologic settings including subduction zone, lower crust-upper mantle, migmatite, pegmatite, porphyry, and orogenic deposits.